2012
DOI: 10.2135/cropsci2012.03.0192
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Seed Yield and Quality as a Response to Field Pennycress Residue

Abstract: Field pennycress [Thlaspi arvense L.; hereafter pennycress) is an oilseed crop being investigated as an off-season biofuel source that can potentially fit into the existing crop rotation cycle with soybean [Glycine max (L.) Merr.]. The objective of this 2-yr study was to evaluate the effect of pennycress residue on seed yield and quality components of soybean planted during five consecutive weeks, from mid-May to mid-June. In 2009 and 2010, the mean soybean dry weight seed yield after pennycress residue for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
59
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 24 publications
0
59
1
Order By: Relevance
“…The pennycress crop establishes a robust vegetative cover prior to winter, providing important ecosystem services such as limiting soil erosion and nutrient run-off. In the spring, pennycress will flower and set seed, yielding upwards of 1,600 pounds per acre of oil-rich seed in time for planting a crop of soybean (Phippen & Phippen, 2012;Sedbrook et al, 2014). Pennycress seed is high in oils that can be readily converted to biodiesel or jet fuel, with the remaining high-protein seed meal having potential as animal feed or feedstock for industrial uses (Evangelista, Isbell, & Cermak, 2012;Fan, Shonnard, Kalnes, Johnsen, & Rao, 2013;Hojilla-Evangelista, Evangelista, Isbell, & Selling, 2013;Moser, Knothe, Vaughn, & Isbell, 2009;Selling, Evangelista, Isbell, & Evangelista, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The pennycress crop establishes a robust vegetative cover prior to winter, providing important ecosystem services such as limiting soil erosion and nutrient run-off. In the spring, pennycress will flower and set seed, yielding upwards of 1,600 pounds per acre of oil-rich seed in time for planting a crop of soybean (Phippen & Phippen, 2012;Sedbrook et al, 2014). Pennycress seed is high in oils that can be readily converted to biodiesel or jet fuel, with the remaining high-protein seed meal having potential as animal feed or feedstock for industrial uses (Evangelista, Isbell, & Cermak, 2012;Fan, Shonnard, Kalnes, Johnsen, & Rao, 2013;Hojilla-Evangelista, Evangelista, Isbell, & Selling, 2013;Moser, Knothe, Vaughn, & Isbell, 2009;Selling, Evangelista, Isbell, & Evangelista, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the US Midwest, pennycress is being developed as a winter-hardy oilseed crop that can be double-and relay-cropped to diversify agroecological systems presently dominated by the summer-annual crops maize and soybean (Moser et al, 2009;Phippen and Phippen, 2012). Pennycress possesses many traits that can support its integration in existing maize-soybean agroecological systems.…”
Section: Field Pennycress -A Promising Vehicle For Diversificationmentioning
confidence: 99%
“…For example, pennycress and soybeans produced 18-20% more oilseed yield per acre than soybean alone, despite modest reductions in soybean yields ( Johnson et al 2015). Trials in a warmer region (Illinois) have shown no soybean yield loss when double cropped with pennycress (Phippen and Phippen, 2012).…”
Section: Field Pennycress -A Promising Vehicle For Diversificationmentioning
confidence: 99%
“…The pennycress crop establishes a robust vegetative cover prior to winter, providing important ecosystem services such as limiting soil erosion and nutrient runoff. In the spring, pennycress will flower and set seed, yielding upwards of 1,600 pounds per acre of oil-rich seed in time for planting a crop of soybean 3,4 . Pennycress seed is high in oils that can be readily converted to biodiesel or jet fuel, with the remaining high-protein seed meal having potential as animal feed or feedstock for industrial uses [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%